2021
DOI: 10.1016/j.jiph.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and epidemiological characteristics of COVID-19 among health care workers in Saudi Arabia: A retrospective cohort study

Abstract: Introduction Novel Coronavirus (SARS-CoV-2) is a highly infectious serious acute respiratory syndrome that has emerged in Wuhan, China, and has spread rapidly throughout the world including Saudi Arabia. An important source of infection of 2019 novel coronavirus (2019-nCoV) is healthcare-associated infection (HAI). Healthcare workers (HCWs) have a greater risk of acquiring COVID-19 infection than the general population. Globally, thousands of HCWs have lost their lives due to COVID-19 infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…Therefore, measures to control community spread will also have a significant impact on infection prevention in HCWs. Similarly, other studies from Saudi Arabia during the first wave of COVID-19 showed 90.6% and 78% of cases among HCWs to be community acquired in origin 19 , 11 . In addition, working in wards/units designated for COVID-19 infected patients was not associated with an increased risk of acquiring COVID-19 infection.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, measures to control community spread will also have a significant impact on infection prevention in HCWs. Similarly, other studies from Saudi Arabia during the first wave of COVID-19 showed 90.6% and 78% of cases among HCWs to be community acquired in origin 19 , 11 . In addition, working in wards/units designated for COVID-19 infected patients was not associated with an increased risk of acquiring COVID-19 infection.…”
Section: Discussionsupporting
confidence: 54%
“…The latter deserves careful planning and mitigation strategies to prevent the loss of the essential HCW forces during pandemics. Several studies from Saudi Arabia reported the increased frequency of COVID-19 among non-Saudi HCWs with coworkers being a common source of spread of infection especially in the setting of hospital-provided accommodations 10 , 11 , 12 . This finding is probably unique to countries with large numbers of expatriate populations working in healthcare settings and surely creates challenges for infection prevention in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, this rate was much lower when compared with the Saudi Arabian nationwide data. A serosurveillance study showed that the overall prevalence of COVID-19 among the Saudi population to be about 11% [ 20 ], and another study involving Saudi healthcare workers showed that 10% of them had the disease [ 21 ]. A high vaccination rate among pilgrims may have made the difference.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, healthcare workers have been identified as one of the groups at greatest risk due to their direct exposure to SARS CoV-2 as part of health care 1-6; Thus, the first reports made in China and later in European countries (7)(8)(9)(10)(11) evidenced the rapid and exponential transmission in healthcare personnel. As of May 7, 2020, health personnel accounted for 22% of COVID-19 cases in Spain 9 .…”
Section: Introductionmentioning
confidence: 99%